Personalizacja – przypadek Netlixa. Branding, kontent, mikrogatunki - Włodek, Patrycja (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2026)
This article examines personalization as a central mechanism in Netflix’s operation, in terms of user interface, branding strategy, and algorithmic content management. Tracing the platform’s historical development and the transformation of the media dispositif, the author argues that personalization has served as Netflix’s core identity marker from the outset, with the brand being built not around content but around a technologically enhanced user experience. The text explores how recommendation systems, microgenres, taste clusters, and algorithmic identities shape a complex structure of classification and reception. Personalization is understood here as a dynamic, multi-layered process embedded in a capitalist logic of datafication, which simultaneously offers users the illusion of autonomy and subjects them to a regime of prediction and engagement optimization. The analysis also addresses the influence of personalization on the production of Netflix Originals, aesthetic homogenization, and the redefinition of genre categories. The article ultimately raises the question of whether personalization functions as a genuine user tool—or as a myth inscribed in the platform’s strategic narrative.